A Perspective on Management of Limb Fractures in Obese Children: Is It Time for Dedicated Guidelines? - Donati, Fabrizio; Costici, Pier Francesco; De Salvatore, Sergio; Burrofato, Aaron; Micciulli, Enrico; Maiese, Aniello; Santoro, Paola; La Russa, Raffaele (Frontiers in Pediatrics, 2020)
Limbs fractures are the most common diseases in pediatric orthopedic. Early and late complications are often not preventable, even when performing the best treatment; furthermore, these illnesses are largely implicated in medico-legal claims. The development of evidence-based guidelines is one of the main goals of medical research. Approved guidelines for diagnosis, treatment and follow up are fundamental to obtain the best results in medical practice. Guidelines in pediatric traumatology have been developed, even though specific conditions, like obesity, could influence their drafting. The cast and fixation systems usually applied in pediatric fracture provide a growth plate sparing, a satisfying reduction and good stress resistance, mostly because of lower bodyweight compared to adults. Several studies suggest that obesity influences the bone quality, the management and the outcomes in case of fracture. High body weight rises the risk of trauma, modifies fracture characteristics and increases the risk of incomplete reduction. Fractures in obese children have a higher rate of complications, regardless of conservative or surgical treatment. In obese children surgical treatment is often indicated than in normal weight ones. Such considerations are valid both for lower and upper limb fracture. The aim of this paper is to discuss recent scientific literature and provide a perspective on benefits of a dedicated approach in the management of obese children. Guidelines update could improve healthcare quality in pediatric setting, also reducing medico-legal implications.